2010
DOI: 10.1007/s10608-010-9337-8
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety Sensitivity, Emotional Avoidance, and PTSD Symptom Severity Among Crack/Cocaine Dependent Patients in Residential Treatment

Abstract: High rates of co-occurring posttraumatic stress disorder (PTSD) have been found among patients receiving treatment for substance use disorders (SUD), and there is evidence that this particular co-occurrence is associated with negative SUD treatment outcomes. Thus, there is utility in establishing the role of psychological vulnerabilities related to PTSD within SUD populations, with the goal of ultimately informing targeted interventions and improving clinical outcomes. Anxiety sensitivity (AS) and emotional av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 80 publications
3
23
0
Order By: Relevance
“…Further, presence of an additional diagnosis (e.g., substance use, mood disorder) was more strongly associated with comorbid PTSD and GAD (Milanak et al 2013). PTSD symptom severity has also been associated with more severe general anxiety Grant et al 2008;Naifeh et al 2012) in military veterans , motor vehicle accident victims (Grant et al 2008), and substance dependent inpatients (Naifeh et al 2012).…”
Section: Comorbidity Between Ptsd Mdd and Gadmentioning
confidence: 99%
“…Further, presence of an additional diagnosis (e.g., substance use, mood disorder) was more strongly associated with comorbid PTSD and GAD (Milanak et al 2013). PTSD symptom severity has also been associated with more severe general anxiety Grant et al 2008;Naifeh et al 2012) in military veterans , motor vehicle accident victims (Grant et al 2008), and substance dependent inpatients (Naifeh et al 2012).…”
Section: Comorbidity Between Ptsd Mdd and Gadmentioning
confidence: 99%
“…Although there is a paucity of data regarding the prevalence of co-morbid anxiety disorders, possibly due to the fact that cocaine is less commonly thought to be consumed in individuals with a pre-disposition for anxiety, a NESARC survey documented that 31% of individuals with cocaine dependence reported lifetime anxiety disorders (Conway, Compton, Stinson, & Grant, 2006) and paranoia has also been documented as occurring in 68% to 84% of patients using cocaine (Morton, 1999). The clinical relevance of this is highlighted by the fact that severity of withdrawal-related anxiety has been found to impact the course, treatment outcome, and prognosis of both syndromes (Naifeh, Tull, & Gratz, 2012; O'Leary et al, 2000) (Sanchez-Hervas & Llorente del Pozo, 2012), particularly in women (Ambrose-Lanci, Sterling, & Van Bockstaele, 2010; Back et al, 2005; Chaplin, Hong, Bergquist, & Sinha, 2008; H. C. Fox & Sinha, 2009).…”
Section: The Role Of Anxiety Symptomatology In Compulsive Cocaine-seementioning
confidence: 99%
“…Similarly, a more recent study found that emotional avoidance and AS were uniquely predictive of PTSD symptom severity in substance dependent patients even when accounting for anxiety severity and participant sex (Naifeh, Tull, & Gratz, 2012). When emotional avoidance and AS were considered simultaneously, AS no longer significantly predicted PTSD severity, suggesting that the relationship between AS and PTSD was indirect through emotional avoidance.…”
mentioning
confidence: 91%